Facsimile imagery analysis on the history of acquired immunodeficiency syndrome - Margarida Maria Rocha Bernardes; Antonio Marcos Tosoli Gomes; Fernando Rocha Porto; Érick Igor dos Santos; Sônia Helena da Costa Kaminitz (Universidade Federal do Ceará, 2016)
Objective: to demonstrate the use of the image as image inductor to the research of social memory in health and nursing from an emblematic image of the history of acquired immune deficiency syndrome. Methods:utilization of a matrix of image analysis with four items about the picture published in the Jornal o Globonewspaper of 09.28.1987, page 13. Results: the results were contextualized to the symbol image of a pandemic, through corresponding public media elements in the 1980s in Brazil. The attitudes of the nursing professional were highlighted, who is said infected by the human immunodeficiency virus in the work space, and this media subject published in a national newspaper. This is photojournalism that can serve as a tool for studies of social memory in health and nursing. Conclusion: the analysis of the matrix is ratified as a research tool of social memory and documentary image, applicable to nursing research.